2010
DOI: 10.1158/1078-0432.ccr-09-1638
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mutated IGHV3-23 Genes in Chronic Lymphocytic Leukemia Identifies a Disease Subset with Peculiar Clinical and Biological Features

Abstract: Purpose: B-cell chronic lymphocytic leukemia (CLL) is a clinically heterogeneous disease whose outcome can be foreseen by investigating the mutational status of immunoglobulin heavy chain variable (IGHV) genes. Moreover, a different prognosis was reported for CLL expressing specific IGHV genes in the context or not of stereotyped B-cell receptors. Here we investigated novel associations between usage of specific IGHV genes and clinical features in CLL.Experimental Design: Among 1,426 CLL-specific IG-rearrangem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 52 publications
5
51
0
Order By: Relevance
“…12,13 However, little is known regarding the capacity of external stimuli to modulate the expression of specific microRNAs and/or microRNA families in CLL. In this regard, studies by our group have recently demonstrated a close correlation between the expression of a particular BCR (that is, IGHV3-23) with relatively higher levels of two key microRNAs (that is, miR-15a and miR-16-1), 14 indicating that the expression of certain microRNAs could be modulated by BCR signals.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…12,13 However, little is known regarding the capacity of external stimuli to modulate the expression of specific microRNAs and/or microRNA families in CLL. In this regard, studies by our group have recently demonstrated a close correlation between the expression of a particular BCR (that is, IGHV3-23) with relatively higher levels of two key microRNAs (that is, miR-15a and miR-16-1), 14 indicating that the expression of certain microRNAs could be modulated by BCR signals.…”
Section: Introductionmentioning
confidence: 92%
“…Additional biological features of CLL cases entering this study, including expression of ZAP-70 and CD38, interphase fluorescence in-situ hybridization for the main chromosomal abnormalities and the experiments for which each sample has been used are listed in Supplementary Table S1. 1,14,15 In all cases, CLL cells were purified by negative selection using anti-CD3, anti-CD14 and anti-CD16 mouse monoclonal antibodies and Dynabeads coated with a pan anti-mouse IgG antibody (Dynal Biotech, Oslo, Norway). 8 The purity of the CLL cells after negative selection was monitored by flow cytometry, and the percentage of CD5 þ /CD19 þ cells exceeded 98% for all the CLL samples from the patients entering the study.…”
Section: Cll Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Moreover, cases with particular B-cell receptor immunoglobulin (BcR IG; eg, those expressing specific IGHV genes) have been reported to not abide by the M-CLL/U-CLL categorization rule. [7][8][9] A paradigmatic example concerns IGHV3-21 gene usage, which has been correlated with shorter overall survival (OS) independently of SHM status. [10][11][12] Interestingly, more than half of CLL cases utilizing the IGHV3-21 gene display highly similar variable heavy complementarity determining region 3 (VH CDR3) sequences and light-chain gene usage [9][10][11][12][13][14] ; thus, they fulfill the criteria of BcR IG stereotypy, a frequent phenomenon in CLL, occurring in ;30% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Our present results demonstrate that TIA1b is inhibitory to VSV replication. Since expression of TIA1 is mediated by many cellular factors including miRNAs (64,65), it would be of interest to examine how hnRNP K regulates or is regulated by these factors, which may provide further understanding of the role of cellular factors involved in VSV replication.…”
Section: Discussionmentioning
confidence: 99%